Analysis of the spatial reasoning of historical Perak Sultanate - Ibrahim, Illyani; Hj. Mohd. Noor, Norzailawati; Jahn Kassim, Puteri Shireen; Abdullah, Alias (2018)
The pattern of buildings location can reflect the identity of the historical buildings to the social relations. The aim of this research is to elucidate the spatial relationship of the historical Sultanate of Perak physical features with the orientation and distance with the other historical buildings in a discrete spatial scales. The objective of this paper is to analyse the spatial orientation and distance between all features and to identify the relationship between the palace and locations’ analysed. Using this notation, the interaction between space and distances are derived to understand the reasoning such location of the historical features. The findings show that i) Istana Iskandariah are located at the hill top ii) most of Rumah Pembesar are facing to the Istana Iskandariah, iii) a linear pattern due to the relocation of palace was during Colonial, iv) Islam are the main connection between palace and people.